Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan pada Restoran Cepat Saji di Kabupaten Tangerang - Dihin Septyanto; Diyna Virya Smarasanta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The fast food industry has grown rapidly driven by urbanization, modern lifestyles, and innovation in menus and service. This industry also faces significant challenges, namely intense competition. Therefore, companies need to improve factors that can strengthen relationships with customers and encourage them to remain loyal. This research aims to analyze the influence of service quality, price and food quality on customer satisfaction and customer loyalty at the Tigaraksa fast food restaurant. This research uses quantitative methods and uses non-probability sampling methods with purposive sampling techniques. The data analysis technique used was Partial Least Square-Structural Equation Modeling (PLS-SEM), with a sample size of 240 respondents. The results of data processing prove that service quality has a positive effect on customer satisfaction. Price has a positive effect on customer satisfaction. Food quality has a positive effect on customer satisfaction. Service quality has a positive effect on customer loyalty. Price has a positive effect on customer loyalty. Food quality has a positive effect on customer loyalty, and customer satisfaction can increase customer loyalty. This research contributes to restaurant managers continuing to improve service quality, setting competitive prices, and ensuring consistent food quality in order to achieve higher customer satisfaction and loyalty.